Evolution of structural, optical properties and electrical transport of NiOX films annealed in different environment - Beisembekov, M.K.; Omarbekova, G.I.; Guchenko , S.A.; Tazhibayev , S.K.; Aimukhanov, A.K.; Afanasyev , D.A.; Nurmakhanova, A.K.; Zeinidenov, A.K. (Recent Contributions to Physics, 2024)
The influence of the annealing medium of thin films of nickel oxide (NiOx) on structural, optical and electrical transport properties is studied in this paper. NiOx films were synthesized by sol-gel method and annealed at a temperature of 300 °C in air, inert nitrogen (N2), oxygen (O2) gases and vacuum. The values of the films thickness were determined from the transverse cleavage of the SEM image. The films thickness depends on the annealing medium. Measurements of the EDX spectra of NiOx films were carried out. Analysis of the quantitative O/Ni ratio showed that the film annealed in an air atmosphere is close to the stoichiometric parameters of NiO. Measurements of the EDX spectra of NiOx films were carried out. According to the Raman spectra, an increase in peak intensities is observed indicating an increase in the density of defects in the film by Ni vacancies depending on the annealing medium. Absorption spectra and Tauc plots of NiOх films were obtained. The optical density of the films depends on the annealing conditions of the films. Data analysis shows that the band gap width depends on the annealing medium and varies from Eg = 3.12 eV to Eg = 3.45 eV. The analysis of the impedance spectra allowed us to estimate the values of the resistances R1 and R2. It is shown that an increase in the resistance of R1 is associated with a decrease in the density of defects in the NiOx film, decrease in the recombination resistance of R2, and an increase in recombination processes at the interface.